2015
DOI: 10.1186/s40064-015-0905-y
|View full text |Cite
|
Sign up to set email alerts
|

Presence and distribution of mosquito larvae predators and factors influencing their abundance along the Mara River, Kenya and Tanzania

Abstract: Among all the malaria controlling measures, biological control of mosquito larvae may be the cheapest and easiest to implement. This study investigated baseline predation of immature mosquitoes by macroinvertebrate predators along the Mara River, determined the diversity of predators and mosquito larvae habitats and the range of their adaptive capacity to water physico-chemical parameters. Between July and August 2011, sampling sites (n=39) along the Mara River were selected and investigated for the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 58 publications
10
37
0
4
Order By: Relevance
“…In Darge, during an extended period without rain, pools of stagnant water formed in the river beds that served as larval breeding habitats. This corroborates with other studies that showed that drying streams [24,30], drying river beds [25] and habitats at river fringes [27] supported the greatest numbers of mosquito larvae during the dry season. During the dry season, areas which were flooded during the rainy season are very important for the quick re-colonization of the larval habitats shortly after the rainfall [25,31].…”
Section: Discussionsupporting
confidence: 92%
“…In Darge, during an extended period without rain, pools of stagnant water formed in the river beds that served as larval breeding habitats. This corroborates with other studies that showed that drying streams [24,30], drying river beds [25] and habitats at river fringes [27] supported the greatest numbers of mosquito larvae during the dry season. During the dry season, areas which were flooded during the rainy season are very important for the quick re-colonization of the larval habitats shortly after the rainfall [25,31].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Fadilah et al () revealed that better water quality can enhance the individual abundance, species richness, and diversity of aquatic insects. Moreover, the results of the present study demonstrate that Culex abundance is negatively correlated with water quality (Table ), as reported by Dida et al (). The structurally complex habitats that contained abundant macrophytes were important for enhancing predator colonization but seemed to deter mosquitoes.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of natural predators of mosquito larvae can contribute to control the population size of malaria vectors, depending on the physicochemical properties of the water habitat (Dida et al 2015). Humidity affects mosquito survival, because under very dry conditions mosquitoes will desiccate (Jawara et al 2008).…”
Section: Natural Environmentmentioning
confidence: 99%